Analysing British Asian national sporting affiliations post-London 2012. Issue 11 (2nd November 2021) - Forbes, Alison
Abstract: London's selection as hosts for the 2012 Olympic Games was a significant moment for Britain. It was a chance to reinforce, through sport, a collective and inclusive British national identity. Most international sporting contests draw on English rather than British loyalties and identity constructions. This might have been especially important for members of the large British Asian diaspora, many of whom feel excluded from ethnically exclusive and narrowly White notions of 'Englishness'. This paper is framed within a post-London 2012 period and examines the role of sport in constructing and negotiating British Asian national identities. Semi-structured interviews were conducted with young British Asians in two English cities. For those who rejected an English national identity through sport, the Games presented an opportunity to connect with a more inclusive British version of sporting allegiance.